Pola Komunikasi Kehidupan Sosial Keagamaan Kawasan Kumuh Kampung Pemulung Kota Bandar Lampung - Fitri Yanti (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2019)
This study aims to analyze the communication patterns of religious social life in the slum areas of scavenger villages in the city of Bandar Lampung. This study uses a qualitative approach that is oriented towards the explanation of natural descriptive data by taking 11 informants as scavenger families. What is the social and social life of the scavengers who are not recognized because of their shortcomings and status that are not the same as the surrounding elite and middle society. The results showed that, the slum dwellers in the village were basically not only